The Effect of Melatonin on Implant Stability and Marginal Bone Level around The Implant - Ravella, Hemanth; Rao, Mulpuri Venkata Ramoji; Manthena, Sathish; Koneru, Suneetha; Preethi, Penubolu Lakshmi; Anumolu, Venkata Naga Sri Harsha (Journal of Dentistry Indonesia, 2022)
Dental implants have been used for missing teeth replacement with a high success rate. Melatonin is an antioxidant and acts as a free radical scavenger. It retards the resorption of bone by regulating RANKL and OPG synthesis, and increases the BIC (Bone to implant contact) and also bone perimeter and bone mineralization. Objective: The aim of the study was to assess if topical melatonin application at the osteotomy site has any influence on the stability and marginal bone level around the implant Methods: In this split mouth double blind randomized control trial 30 implants were placed on either side of the mandible in which test sites were irrigated with melatonin solution prior to the implant placement and the control site on the other side was irrigated with normal saline. Crestal bone level and implant stability assessment was done at baseline and 3 months. Results: A significant difference was observed between the groups with respect to crestal bone loss scores at 3 months. Regarding implant stability a significant difference(p<0.05) was observed within the groups at baseline and 3 months and also between the groups at 3 months only. Conclusion: Melatonin showed a statistically significant reduction in crestal bone loss and an increase in implant stability.